Determination of viral factors associated with dengue virus infection and disease severity - Suppiah, Jeyanthi (2019)
Malaysia has experienced an unprecedented dengue outbreak between the years 2014 and 2015. The mortality rate of dengue was still higher in 2016 compared to 2014 indicating the continuity of the outbreak. There is an increasing concern that patient management and environmental control alone are insufficient to overcome the current dengue epidemic in Malaysia. Importantly, insight into the substantial progress of the disease burden despite implementation of fogging and well-managed health care system should be addressed. Could the answer lie within the dengue virus (DENV) itself? Has the virus become virulent than we can imagine? Thus, the proposed study is aimed to identify the viral factors contributing to dengue virus infection and severity, especially during an outbreak period. The present study focused on identifying the pattern of dengue serotype and genotype distribution retrospectively from the year 2014 to 2017 in Malaysia. Dengue sera from dengue confirmed patients were obtained from three localities, which include Hospital Serdang, Hospital Ampang and Institute for Medical Research. The study also attempted to associate the clinical spectrums and severity of patients with the aforementioned serotype and genotype distribution. Subsequently, viral replication and infectivity kinetics were compared between dengue isolates from severe and non-severe cases as well as among genotypes. Finally, dengue subgenomic RNA (sfRNA) was identified and quantified using self-designed primers against all four serotypes to deduce the role of the sfRNA in disease severity. The study findings indicated that DENV 1 genotype I was the predominant serotype and genotype during the recent dengue outbreak in Malaysia. This reflected a serotype shift in replacing the predominant DENV 2 that existed prior to the outbreak. The current trend denotes that serotype replacement, is predicted to re-occur once the current outbreak subsides. The re-emergence of DENV 3 genotype I was observed during this period, where it should be cautiously monitored, as adaption to become more virulent is possible. Comparison between the dengue serotypes and genotypes with disease spectrum revealed that the clinical characteristics of dengue patients were serotype and genotype-specific. DENV 1 and DENV 3 were common in patients with mild infection whereas DENV 2-infected patients significantly exhibited warning signs and presented with severe dengue. DENV 3 genotype I was frequently observed in patients with myalgia whereas DENV 3 genotype III was common in patients with arthralgia. The in-vitro phenotypic characterization of dengue isolates from severe cases demonstrated a slow and prolonged replication. The infectivity kinetics lasted up to day six whereas the isolates from non-severe cases exhibited an early rise in the replication and infectivity kinetics but unable to sustain towards the end. The replication and infectivity kinetic trends varied with respect to dengue genotypes, consistent with the circulating predominant genotypes. Involvement of sfRNA in the disease severity was evidenced through higher copy numbers in severe dengue than non-severe dengue isolates. In conclusion, the results demonstrated that viral factors such as serotype shift, re-emergence of certain genotypes, efficient replication and infectivity mechanism and sfRNA collectively contribute towards dengue clinical manifestations and disease severity. Complete eradication of these factors is difficult as they are rather internal. Nonetheless, manipulating and predicting their behaviour may aid in early detection of disease progression and developing deeper understanding on dengue pathogenesis. Furthermore, the clinical symptoms of severe dengue infection only manifest at later stage of dengue infection. Therefore, information on the serotype or genotype-specific dengue manifestations and monitoring of viral genomic copy numbers and sfRNA levels may serve as early surrogate markers to predict the disease progression.